Tantangan dan Peluang Metode Tarjamah dalam Pengajaran Bahasa Arab di Era Teknologi Digital - Bertuah, Ilham Air; Zulhaiki, Zulhaiki (STAINI Press, 2026)
This study aims to explore the challenges and opportunities of employing the tarjamah (translation) method in teaching Arabic in the digital technology era. The research was conducted through a literature review by analyzing various sources that discuss the integration of technology in language education. The findings indicate that the tarjamah method remains relevant in Arabic language instruction, provided it is adapted to current technological developments. The use of digital media—such as interactive learning applications, visual aids, and audiovisual tools—can enhance the effectiveness of this method by offering a more contextual and engaging learning experience for students. Nevertheless, several challenges must be addressed. A primary issue is the need for training teachers and students to critically evaluate the outputs of machine translation, which are often inaccurate. Furthermore, it is essential to instill the understanding that technology serves merely as a tool, not a replacement for the critical thinking process required to deeply comprehend texts. Therefore, an innovative and thoughtful approach is necessary when integrating technology, so as not to compromise the core essence of the tarjamah method. Teaching Arabic through the tarjamah approach in the digital age should strive to harmoniously combine the strengths of traditional methods with the sophistication of modern technology.